Hubungan Karakteristik Lingkungan Rumah Dengan Kejadian Demam Berdarah Dengue Pada Anak Usia Sekolah - Ismayanti, Galuh; Salsabila, Nola; Anjani, Olivia (JUKEJ : Jurnal Kesehatan Jompa, 2025)
The purpose of this study was to determine and analyze the relationship between the characteristics of the home environment and the incidence of Dengue Hemorrhagic Fever in school-age children, to identify the characteristics of the home environment including sanitation conditions, the existence of water reservoirs, and environmental cleanliness. Method: The research design used is a descriptive analytical research design with a Cross Sectional approach. The population used in this study were school-age children who were treated with a diagnosis of fever at Demang Sepulau Raya Regional Hospital. The number of samples in this study was 33 respondents. The sampling technique used Purposive Sampling. Statistical analysis was carried out using the SPSSS 20 program. The statistical test used was the chi square test with a significance level of 95%. The p value is considered significant if <0.05. Results: This study found that the average age of children experiencing DHF was 8.8 years. The youngest child experiencing DHF was 6 years old and the oldest was 12 years old (CI 8.13 - 9.57). The gender of children who experienced DHF the most was female, namely 17 people (51.5%). The level of education (father) of the respondents who suffered from DHF was the low education category, namely 31 people (94%). The education level (mother) of the respondents who suffered from DHF was the low education category, namely 28 people (84.8). The frequency of father's work was the most in the working category, as many as 30 people (90.9%) and the frequency of mother's work was the most in the unemployed category, as many as 19 people (57.6%). There was a relationship between the characteristics of the home environment and the incidence of DHF in children, obtained statistical test results p value 0.008 (α <0.05). Statistically, it was concluded that there was a significant relationship between the characteristics of the home environment and the incidence of DHF in school-age children. Conclusion: This study can be concluded that the characteristics of the average age of respondents is 8.85 years, the most gender is female, the father's education level is low, the mother's education level is low, the father's employment status is working, and the mother's employment status is not working. The most characteristic of the home environment is not good. There is a relationship between the characteristics of the home environment and the incidence of DHF in school-age children. Keywords: Home Environment, Dengue Fever, and School-Age Children